HUBUNGAN AKTIVITAS FISIK PEKERJA TANI DENGAN KEJADIAN OSTEOARTHRITIS - Ai Utari; Florentina Dian Maharina; Friska Sinaga (Jurnal Kesehatan, 2021)
Osteoarthritis (OA) is a chronic inflammatory disease of the joints due to cartilage breakdown. OA that is left untreated can cause pain, stiffness, swelling, and can lead to disability. Osteoarthritis can occur due to one of the factors which is physical activity that is too heavy. Physical activity and work as farmers and coolies can burden the joints that support the body, especially the knees and waist so that it is very risky to experience osteoarthritis. The purpose of this study was to determine the correlation between physical activity of farm workers that resulted in the incidence of osteoarthritis. This research is a quantitative research, the design of this research is descriptive correlation with cross sectional approach. The number of samples used as many as 113 respondents farm workers. Sample selection using non-probability sampling technique in the form of accidental sampling. Data were collected using the IPAQ questionnaire for measuring physical activity for the last 7 days, and the WOMAC questionnaire for assessing the incidence of osteoarthritis. The questionnaire was distributed directly and analyzed using the Spearman Rank test. The results of statistical tests obtained p-value 0,01 (p < 0,05) which indicates a correlation between physical activity of farm workers with the incidence of osteoarthritis.it is hope that village heads and health workers cam carry out health education activities, especially regarding osteoarthritis and how to prevent it so as not to increase the incidence of osteoarthritis in farmers.